Microwave Assisted Extraction Of Crude Drugs - JOSHI UTTARA,; WARE LEENA,; UPADHYE MOHINI, (International Journal of Pharma and Bio Sciences, 2010)
In recent years, the use of microwave for extraction of constituents from plant material has shown tremendous research interest and potential. The traditional techniques of solvent extraction of plant materials require long extraction time and have low efficiency. Moreover, many natural products are thermally unstable and may degrade during thermal extraction. Microwave extraction can be the better alternative to conventional extraction. Microwave assisted extraction requires shorter time, less solvents, higher extraction rate and better products with lower loss. There is less risk of decomposition and oxidation of phytoconstituents. In the present study widely used plants were selected on the basis of their phytochemical profile and an attempt has been made to make use of microwave for extraction of four indigenous drugs viz Neem, Clove, Amla and Tea. The powders of these drugs were subjected to percolation using water.